ANALISIS KEPUTUSAN MAHASISWA DALAM MEMILIH INSTITUT WIDYA PRATAMA DAN IMPLIKASINYA TERHADAP STRATEGI PEMASARAN - VICTORIANUS ARIES SISWANTO; Tri Pudji Wahjuningsih; Nur Ika Royanti (P3M Institut Widya Pratama, 2026)
This study aims to examine the factors influencing students’ decision-making in choosing Institut Widya Pratama (IWIMA) Pekalongan and their implications for the institution’s marketing strategy formulation. The research is motivated by the declining trend in new student admissions in recent years, highlighting the need to analyze student behavior as consumers of higher education services. This study employs a descriptive approach using a mixed-method design (qualitative and quantitative). Data were collected through a Google Form questionnaire distributed to 102 active students in semesters 3, 5, and 7 from the Informatics Engineering and Information Systems study programs. The data analysis technique used descriptive percentage analysis to identify the dominant factors influencing campus selection decisions. The results indicate that the primary source of information about IWIMA is recommendations from friends and family (62.6%), followed by social media (33.3%) and brochures (20.2%). The dominant factors in choosing a study program are students’ personal interest (54.9%), the desire to deepen knowledge in computer science (45.1%), and consideration of job opportunities after graduation (37.3%). The decision to enroll at IWIMA is mainly influenced by proximity to parents (38.2%), followed by interest in the study program (30.4%), career opportunities (29.4%), and the strategic location of the campus (27.5%). The level of student satisfaction with IWIMA tends to be neutral (44.1%), while 32.4% of students are satisfied and 13.7% are very satisfied, with the remainder expressing dissatisfaction. These findings suggest that IWIMA’s marketing strategy should focus on strengthening word-of-mouth promotion, optimizing social media utilization, improving the quality of academic services and campus facilities, and enhancing collaboration with stakeholders to increase student satisfaction, institutional image, and competitiveness in attracting prospective students.